Electronic Structure Engineering of Single‐Atom Tungsten on Vacancy‐enriched V3S4 Nanosheets for Efficient Hydrogen Evolution - Min Xi; Hua Zhang; Lingfeng Yang; Youyu Long; Yifan Zhao; Anran Chen; Qiaozhi Xiao; Tingting Liu; Xuechun Xiao; Guangzhi Hu (Advanced Science)
Abstract Constructing single‐atom catalysts (SACs) and optimizing the electronic structure between metal atoms and support interactions is deemed one of the most effective strategies for boosting the catalytic kinetics of the hydrogen evolution reaction (HER). Herein, a sulfur vacancy defect trapping strategy is developed to anchor tungsten single atoms onto ultrathin V3S4 nanosheets with a high loading of 25.1 wt.%. The obtained W‐V3S4 catalyst exhibits a low overpotential of 54 mV at 10 mA cm−2 and excellent long‐term stability in alkaline electrolytes. Density functional theory calculations reveal that the in situ anchoring of W single atoms triggers the delocalization and redistribution of electron density, which effectively accelerates water dissociation and facilitates hydrogen adsorption/desorption, thus enhancing HER activity. This work provides valuable insights into understanding highly active single‐atom catalysts for large‐scale hydrogen production.